PERBEDAAN PENGARUH OPEN KINETIC CHAIN EXERCISE DAN CLOSE KINETIC CHAIN EXERCISE TERHADAP KEKUATAN OTOT QUADRICEPS FEMORIS PASCA OPERASI ANTERIOR CRUCIATE LIGAMEN DITINJAU DARI USIA: The Effect of Open Kinetic Chain Exercise and Close Kinetic Chain Exercise on Strength Quadriceps Femoris Muscle Post Anterior Cruciate Ligament Surgery in terms of Age - Miftahudin Sigit; Muchsin Doewes; Hanik Liskustyawati (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
This research is an experimental research. The sample is post-Anterior Cruciate Ligament surgery patients at the Solo Sport Physiotherapy Clinic as many as 16 people including Open and Close exercise categories and based on adolescent and adult age categories. Samples were taken using purposive sampling technique. The variables in this study include: 1) Quadriceps Femoris Muscle Strength (Y); 2) Open Exercise (a1); 3) Close Exercise (a2); and 4) Age (b). Research data were obtained from measurements using an Electromyograph. Hypothesis testing using two-way Anova test and t test. Conclusion, (1) There is a difference in the effect of quadriceps femoris muscle strength after being given open kinetic chain and close kinetic chain exercises in ACL postoperative patients. Which means that close kinetic chain training has a better improvement than open kinetic chain in ACL postoperative patients. (2) There are differences in the effect of quadriceps femoris muscle strength in adolescent and adult athletes. Which means that adult athletes have a better increase in quadriceps femoris muscle strength compared to adolescent athletes. (3) There is no interaction between open kinetic chain and close kinetic chain training methods with adolescent and adult age on increasing quadriceps muscle strength.